Odpowiedzi

2009-11-27T18:04:36+01:00
2x-y=3 (metoda przeciwnych wspolczynnikow, nie trzeba nawet nic
x+y=6 przeksztalcac)
+ _____
3x=9 /:3
x=3

x+y=6
3+y=6
y=6-3
y=3

odp. x=3, y=3
Najlepsza Odpowiedź!
2009-11-27T18:12:14+01:00
2x-y=3 |+y
x+y=6

2x=3+y |:2
x+y=6

x= 3+y /2 <- ulamek
3+y /2 +y=6 |*2

x= 3+y /2 <- ulamek
3+y+2y=12 |-3

x= 3+y /2 <- ulamek
y+2y=12-3

x= 3+y /2 <- ulamek
3y=9 |:3

x= 3+y /2 <- ulamek
y= 3

x= 3+3 /2 <-ulamek (podstawiamy)
y= 3

x= 3
y=3
2009-11-27T18:16:05+01:00
2x-y=3
x+y=6

3x=9|:3
x=3

x+y=6
3+y=6
y=3
x=3